2015
DOI: 10.1007/s13143-015-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Origin, evolution and structure of meso-α-scale lows associated with cloud clusters and heavy rainfall over the Korean peninsula

Abstract: An investigation was conducted to describe the locations of initial occurrence, evolution and structure of meso-α-scale lows (MLs) associated with cloud clusters and heavy rainfall over the Korean Peninsula using observation and reanalysis data. We selected 29 heavy rainfall events associated with MLs during the 10-year period of 2001-2010. The locations of initial ML occurrence are widely spread from the eastern flank of the Tibetan Plateau to the Yellow Sea. These locations are grouped into 3 regions: 1) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…A heavy rainfall episode is defined by a 24-hour rainfall amount greater than 80 mm at a minimum of one station. Seventeen CCMT episodes have been selected for the 11-year period based on the definition of CCMTs by Shin and Lee (2015) (Table 1). It can be found from Table 1 that the maximum hourly rainfall amount occurs mostly during 0000 -1200 LST (LST = UTC + 9 hours) in 14 episodes, where 10 of them have maxima during 0300 -0900 LST (1800 -0000 UTC).…”
Section: Diurnal Variations In Rainfall During Ccmt Episodesmentioning
confidence: 99%
See 2 more Smart Citations
“…A heavy rainfall episode is defined by a 24-hour rainfall amount greater than 80 mm at a minimum of one station. Seventeen CCMT episodes have been selected for the 11-year period based on the definition of CCMTs by Shin and Lee (2015) (Table 1). It can be found from Table 1 that the maximum hourly rainfall amount occurs mostly during 0000 -1200 LST (LST = UTC + 9 hours) in 14 episodes, where 10 of them have maxima during 0300 -0900 LST (1800 -0000 UTC).…”
Section: Diurnal Variations In Rainfall During Ccmt Episodesmentioning
confidence: 99%
“…Heavy rainfall over the Korean peninsula during summer generally occurs over or near the northwestern edge of the western Pacific subtropical high (WPSH), where a wide band of southwesterlies can be found. As a meso-α-scale depression moves or develops along the northwestern edge of the WPSH, southwesterlies to the southeast of the depression become stronger (Shin and Lee 2015). Various studies have also found the importance of strong southwesterlies or low-level jets (LLJs) for heavy rainfall over the Korean peninsula (e.g., Kim et al 1983;Hwang and Lee 1993;Chen, S. et al 1999;Jung et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloud clusters are the major type of MCSs over the Korean peninsula, and Shin and Lee (2015) classified CCs into two types: those associated with meso-α-scale lows (CCMLs) and mesoscale troughs (CCMTs). The term "mesoscale trough" defines a mesoscale depression that does not develop into a meso-ɑ-scale closed-isobar system.…”
Section: Introductionmentioning
confidence: 99%
“…For Northeast Asia, choosing a wide model domain may make the Tibetan Plateau (TP), Manchuria and the Kamchatka Peninsula (MK) included in the model domain. The TP can induce peculiar air flows due to strong radiative forcing related to its high elevation and vigorous dynamical forcing in steep slope regions at the lee side and stagnation regions over the eastern flank at the Sichuan Basin (SB) (e.g., Jiang, Li, Zhao, & Koike, ; Shin & Lee, ; Tao & Ding, ; Wang & Orlanski, ). Numerical simulations of such unique flow structures are challenging, and inaccurate simulations may produce unreliable predictions for Northeast Asia (Zhang, Li, Fu, Liu, & Li, , and references therein).…”
Section: Introductionmentioning
confidence: 99%